Efektivitas Pelayanan Keluarga Sejahtera Melalui Website Siap Bahagia di Perwakilan BKKBN Provinsi Jawa Timur - Nipfasari, Selvia; Meirinawati, Meirinawati (Publika, 2024)
The aim of this research is to determine the effectiveness of online family welfare services through the Siap Bahagia website developed by the East Java Provincial Representative of BKKBN. The Covid-19 pandemic has hindered offline family welfare services, affecting vulnerable families in East Java. To address this challenge, the East Java Provincial Government, through BKKBN East Java, developed the Siap Bahagia online service to enhance family welfare services. This study employs a qualitative method using website effectiveness theory measured based on performance, information, and economy indicators. The results of this research indicate that the effectiveness of the Siap Bahagia website is still low due to the limited number of visitors, lack of socialization, slow counselor responses, technical disruptions, and lack of variety and updates in articles. However, the website still provides benefits as it is accessible online and free of charge. This research recommends increasing socialization efforts, improving website security, speeding up counselor responses, and routinely updating article content by BKKBN East Java.